2016
DOI: 10.1001/jamacardio.2016.3030
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Biomarker Assessments in Patients With Type 2 Diabetes at High Cardiovascular Risk

Abstract: clinicaltrials.gov Identifier: NCT01107886.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 40 publications
2
78
0
2
Order By: Relevance
“…In older adults, cardiovascular and in-flammatory biomarkers are related to CVD outcomes over a relatively short follow-up interval. 8 Although adolescents with T2D have a significant lifetime risk for CVD, they may have a lower short-term risk for adverse outcomes than adults. These biomarkers also have been associated with other adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In older adults, cardiovascular and in-flammatory biomarkers are related to CVD outcomes over a relatively short follow-up interval. 8 Although adolescents with T2D have a significant lifetime risk for CVD, they may have a lower short-term risk for adverse outcomes than adults. These biomarkers also have been associated with other adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…57 In adults with T2D, measurement of cardiovascular and inflammatory biomarkers adds to CVD risk stratification. 8,9 …”
mentioning
confidence: 99%
“…However, as the incidences of outcomes differ between patients with HF8 and patients with a recent ACS9 in a stable phase, it is less established how natriuretic peptides are associated with cardiovascular outcomes, especially subsequent MI and stroke, in the latter population 3, 10, 11, 12, 13, 14. Concentrations of natriuretic peptides may be affected by both asymptomatic myocardial ischemia15, 16 and atrial fibrillation,17, 18 which could make BNP and NT‐proBNP relevant as predictors of MI and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Finally in 2015, the TECOS trial, conducted in 14,671 patients with T2D, showed that the DPP-4i sitagliptin, compared to placebo, had no effect on a composite endpoint made of cardiovascular death, nonfatal myocardial infarction, nonfatal stroke, or hospitalization for unstable angina during a follow-up of 3 years (22). These disappointing results were further complicated by the finding, in the SAVOR trial, of a 27% relative excess risk of hospitalization for heart failure associated with the use of saxagliptin (23).…”
Section: Lack Of Clinical Evidencementioning
confidence: 99%